Correlation between the structural, morphological, optical, and electrical properties of In2O3 thin films obtained by an ultrasonic spray CVD process. (August 2015) - Bouhdjer, A.; Attaf, A.; Saidi, H.; Bendjedidi, H.; Benkhetta, Y.; Bouhaf, I.
Abstract Indium oxide (In2O3) thin films are successfully deposited on glass substrate at different deposition times by an ultrasonic spray technique using Indium chloride as the precursor solution; the physical properties of these films are characterized by XRD, SEM, and UV-visible. XRD analysis showed that the films are polycrystalline in nature having a cubic crystal structure and symmetry space group Ia3 with a preferred grain orientation along the (222) plane when the deposition time changes from 4 to 10 min, but when the deposition time equals 13 min we found that the majority of grains preferred the (400) plane. The surface morphology of the In2O3 thin films revealed that the shape of grains changes with the change of the preferential growth orientation. The transmittance improvement of In2O3 films was closely related to the good crystalline quality of the films. The optical gap energy is found to increase from 3.46 to 3.79 eV with the increasing of deposition time from 4 to 13 min. The film thickness was varied between 395 and 725 nm. The film grown at 13 min is found to exhibit low resistivity (10−2 Ω·cm), and relatively high transmittance (∼ 93%).